2014
DOI: 10.1111/geb.12260
|View full text |Cite
|
Sign up to set email alerts
|

Can we derive macroecological patterns from primary Global Biodiversity Information Facility data?

Abstract: AimTo determine whether the method used to build distributional maps from raw data influences the representation of two principal macroecological patterns: the latitudinal gradient in species richness and the latitudinal variation in range sizes (Rapoport's rule).Location World-wide. MethodsAll available distribution data from the Global Biodiversity Information Facility (GBIF) for those fish species that are members of orders of fishes with only marine representatives in each order were extracted and cleaned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
77
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(79 citation statements)
references
References 41 publications
1
77
0
1
Order By: Relevance
“…We used an alpha level of 6 degrees, as recommended by Garcia-Rosello et al 65 , using the ModestR software 66 . We then identified as possible outliers the occurrences falling outside the EOOs.…”
Section: Technical Validationmentioning
confidence: 99%
“…We used an alpha level of 6 degrees, as recommended by Garcia-Rosello et al 65 , using the ModestR software 66 . We then identified as possible outliers the occurrences falling outside the EOOs.…”
Section: Technical Validationmentioning
confidence: 99%
“…2; e.g. García-Roselló et al 2015). Some studies use ocean depth, often in addition to surface variables, in an attempt to account for the third dimension.…”
Section: Open Pen Access Ccessmentioning
confidence: 99%
“…We removed duplicate occurrences of recorded data for species in 10.0-arc-minute grid cells (16 km at the equator) to avoid any georeferencing errors (Merow et al 2013). Previous studies have shown that using species with more than 100 records as input for SDMs decrease the negative effect of sampling bias on their performance (Wisz et al 2008;Fourcade et al 2014;García-Roselló et al 2014). We examined enough occurrence records of TPIs to cover the present distributions of species as given in data from ISSG.…”
Section: Species Datamentioning
confidence: 99%